Characterization of 1H NMR and 13C NMR Spectrometry and Antibacterial Activities of 4-tert-Butylbenzoyl Amoxicillin - Hadi Barru Hakam Fajar Siddiq; Dewi Rashati; Siti Nur Azizah (Sanata Dharma University, 2022)
The synthesis of 4-tert-butylbenzoyl amoxicillin has been done by reacting amoxicillin with 4-tert-butylbenzoyl chloride. The product was characterized using proton and carbon-13 spectrometry. Antibacterial activity of 4-tert-butylbenzoyl amoxicillin against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus was tested using paper disk diffusion method. Results showed that 4-tert-butylbenzoyl amoxicillin had a specific spectrum activity. Antibacterial test of 4-tert-butylbenzoyl amoxicillin showed clear zones around the disc paper for Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. The study results indicated 4-tert-butylbenzoyl amoxicillin has antimicrobial properties but is categorized as a less-effective antibiotic agent based on the response to bacterial growth inhibition.